Environmental exposure to perchlorate, nitrate and thiocyanate, and thyroid function in Chinese adults: A community-based cross-sectional study - King, Lei; Wang, Qiang; Xia, Lili; Wang, Pei; Jiang, Guanhua; Li, Wanyi; Huang, Yue; Liang, Xiaoling; Peng, Xiaolin; Li, Yonggang; Chen, Liangkai; Liu, Liegang (Environment international, 2023)
[Display omitted] •Exposure to perchlorate, nitrate, and thiocyanate was ubiquitous in the Chinese adult population.•Urinary perchlorate, nitrate, and thiocyanate were associated with significant changes in thyroid function markers.•Co-exposure to three goitrogenic anions was inversely associated with serum FT4, TT4, and FT3. Evidence on environmental exposure to perchlorate, nitrate, and thiocyanate, three thyroidal sodium iodine symporter (NIS) inhibitors, and thyroid function in the Chinese population remains limited. To investigate the associations of environmental exposure to perchlorate, nitrate, and thiocyanate with markers of thyroid function in Chinese adults. A total of 2441 non-pregnant adults (mean age 50.4 years and 39.1% male) with a median urinary iodine of 180.1 μg/L from four communities in Shenzhen were included in this cross-sectional study. Urinary perchlorate, nitrate, thiocyanate, and thyroid profiles, including serum free thyroxine (FT4), total thyroxine (TT4), free triiodothyronine (FT3), total triiodothyronine (TT3), and thyroid stimulating hormone (TSH), were measured. Generalized linear model was applied to investigate the single-analyte associations. Weighted quantile sum (WQS) regression and Bayesian kernel machine regression (BKMR) models were used to examine the association between the co-occurrence of three anions and thyroid profile. The median levels of urinary perchlorate, nitrate, and thiocyanate were 5.8 μg/g, 76.4 mg/g, and 274.1 μg/g, respectively. After adjusting for confounders, higher urinary perchlorate was associated with lower serum FT4, TT4, and TT3, and higher serum FT3 and TSH (all P < 0.05). Comparing extreme tertiles, subjects in the highest nitrate tertile had marginally elevated TT3 (β: 0.02, 95% CI: 0.00–0.04). Each 1-unit increase in log-transformed urinary thiocyanate was associated with a 0.04 (95% CI: 0.02–0.06) pmol/L decrease in serum FT3. The WQS indices were inversely associated with serum FT4, TT4, and FT3 (all P < 0.05). In the BKMR model, the mixture of three anions was inversely associated with serum FT4, TT4, and FT3. Our study provides evidence that individual and combined environmental exposure to perchlorate, nitrate, and thiocyanate are associated with significant changes in thyroid function markers in the Chinese population with adequate iodine intake.